Peptides and peptidomimetics in the development of hydrogels towards the treatment of diabetic wounds - Ana Gomes; Paula Gomes (Current Research in Biotechnology)
Diabetic foot ulcers are a major complication of diabetes and a particularly complex type of chronic wounds, as most diabetes-related physiological dysregulations impair healing and increase the risk of infection. Despite many health literacy initiatives have been deployed to promote both the prevention and the proper management of diabetic foot ulcers, these remain a serious healthcare problem whose incidence is rising. This demands not only for a continuous updating of guidelines for adequate interventions in healthcare facilities, but also for new topical treatments able to improve the health and well-being of the patients. In this later case, current options include topical oxygen therapy, negative pressure wound therapy, wound dressings of different types, and topical gels. Due to the tremendous potential of hydrogel-based dressings for diabetic wound treatment, several hydrogels from either natural or synthetic origin have been explored. The hydrogel polymeric matrices can be loaded with many diverse molecules (cargoes) eventually combining distinct therapeutic actions. In this context, peptides are gaining relevance, which is not limited to those used as bioactive cargoes, since self-assembling peptides able to form hydrogels are also under the spotlight. This review focuses on the studies reported over the last decade where peptide-loaded or peptide-derived hydrogels have been tested in vivo for topical treatment of diabetic wounds and further explores the potential of peptidomimetics to expand the portfolio of hydrogel-based treatments for diabetic foot ulcers.